2018
DOI: 10.1080/01634372.2018.1478352
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness in senior housing communities

Abstract: There are many studies on loneliness among community-dwelling older adults; however, there is limited research examining the extent and correlates of loneliness among older adults who reside in senior housing communities. This study examines the extent and correlates of loneliness in three public senior housing communities in the St. Louis area. Data for this project was collected with survey questionnaires with a total sample size of 148 respondents. Loneliness was measured using the Hughes 3-item loneliness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 38 publications
4
21
0
Order By: Relevance
“…Even though senior housing communities are congregate living settings, social isolation from others does occur (H. O. Taylor et al, 2016; H. O. Taylor, Wang & Morrow-Howell, 2018).…”
Section: Nursing Homes and Congregate Living Settingsmentioning
confidence: 99%
“…Even though senior housing communities are congregate living settings, social isolation from others does occur (H. O. Taylor et al, 2016; H. O. Taylor, Wang & Morrow-Howell, 2018).…”
Section: Nursing Homes and Congregate Living Settingsmentioning
confidence: 99%
“…Furthermore, loneliness only correlates -0.11, -.25 and -.24 with size, quality and frequency of social networks, respectively (Rico-Uribe et al, 2015), indicating small effect sizes. Taylor et al, (2018) also found that loneliness is predictive of mental and physical health, but that social support and engagement were not. This speaks to the true importance of the Java Music Club reducing perceived loneliness, despite no change in social support.…”
Section: Discussionmentioning
confidence: 95%
“…A main motivating factor in relocating to a retirement village is social connection (Roy et al, 2018). However, as Boyd and colleagues (2020) found in their assessment of retirement village residents, levels of loneliness in this population remain high, and likely higher than those found in the broader older population (Gray, 2015;Taylor et al, 2018).…”
Section: It Takes (More Than) a Villagementioning
confidence: 98%